I love you already! - John, Jory; Davies, Benji (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
"All Bear wants is to spend a pleasant day alone, but Duck really wants to hang out"--
Keywords: Friendship -- Fiction; Individuality -- Fiction; Bears -- Fiction; Ducks -- Fiction; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Animals / Bears; JUVENILE FICTION / Animals / Ducks, Geese, etc..; Humorous fiction